Half-metallic alloys: electronic structure, magnetism and spin polarization - P.H. Dederichs; Galanakis, I.; P. Mavropoulos (JOURNAL OF ELECTRON MICROSCOPY, 2005)
Using the state-of-the-art screened Korringa-Kohn-Rostoker Green function method we study the electronic and magnetic properties of NiMnSb and similar Heusler alloys. We show that all these compounds are half-metals, e.g. the minority-spin band is semiconducting and the Fermi level falls within this gap resulting in 100% spin polarization at the Fermi level. The total spin moment M-t shows the so-called Slater-Pauling behaviour and scales with the total valence charge Z(t) following the rule M-t = Z(t) - 18 for half and M-t = Z(t) - 24 for full Heusler alloys. These rules are connected to the origin of the gap. Finally we show that the inclusion of the spin-orbit interaction in our calculations kills the half-metallic gap but the spin-polarization at the Fermi level can be still very high, similar to 99% for NiMnSb, but much lower for a half-metallic compound like zinc-blende MnBi (77%).